The Effects of Moderation of the Government's Role in Economic Needs, Accessibility and Business Capital for Street Vendors - Anggit Wismantoro; Kiromim Baroroh (International Journal of Economics and Management Sciences, 2025)
This study aims to determine the role of the government in moderating the influence of economic needs, accessibility, business capital on the existence of street vendors in Bekasi City. This research is a quantitative research. The subjects in this study were street vendors in Bekasi City. The population in this study was 15,402 street vendors, based on data from the Bekasi City Cooperative and Small Business Office. The results of the validity test of the person correlation are that all variables count > rtabel, a(0.05) and the reliability test of all these variables are above 0.600. The number of samples in this study was 390 street vendors. The sampling technique uses cluster sampling. |The data analysis technique used was multiple linear regression analysis and moderating regression analysis (MRA) using the help of IBM SPSS Statistics version 26 for windows.The aims of this research are as follows: (1) Economic needs affect the existence of street vendors in Bekasi City with a parameter coefficient value of 0.179 with a significant level of 0.000<0.05 (2) Accessibility has an effect on the existence of street vendors in Bekasi City with a parameter coefficient value of 0.211 with a significant level of 0.000 < 0.05 (3) Business capital has an effect on the existence of street vendors in Bekasi City with a parameter coefficient value of 0.184 with a significant level of 0.000 < 0.05 (4) The role of the government as a moderating variable (economic needs *existence of street vendors) is able to moderate the effect of economic needs on the existence of street vendors in Bekasi City with a parameter coefficient value of 0.129 with a significant level of 0.034 < 0.05 (5) The role of the government as a moderating variable (accessibility*existence of street vendors) is able to moderate the effect of accessibility on the existence of street vendors with a parameter coefficient value of 0.183 with a parameter coefficient value of 0.183 with a significant level of 0.005 < 0.05 (6) The role of the government as a moderating variable (capital*existence of street vendors) is able to moderate the effect on the existence of street vendors with a parameter coefficient value of 0.222 with a significant level of 0.019 < 0.05